Entre o papel e a prática: as incongruências na produção do espaço da área central de Campina Grande-Paraíba - Bomfim, Leticia Barbosa (2024)
This research addresses the issue of spatial production in central areas, focusing on the case of Campina Grande, a city that exerts significant regional influence in the urban hierarchy, particularly in Paraíba. When discussing the central area, we refer to various processes to which this spatiality is subject: sometimes of valorization, sometimes of devaluation; processes of permanence and transformation; competitions between more profitable uses, new and old properties; different applicable regulations; vacancies and intensified land use; or even areas undergoing demolition processes, becoming market reserves for new real estate interests. In this context, different urban agents are observed in Campina Grande, supported by public authority actions aimed at maintaining this main center as an attractive area for real estate production. However, such interest is marked by conflicting or incongruent relationships with urban and heritage guidelines, especially in the real estate production occurring after 2005 around the Açude Velho, an old water reservoir that has become the city's main "postcard." The hypothesis here is that, between the theory and the practice being executed in Campina Grande, there are agents who act and influence the urban policy process, involving public and private interests, legislative changes, and the weakening of incident regulations with the approval of projects contrary to the regulatory framework. Thus, the general objective of the research is to analyze the production of urban space in the central area of Campina Grande from the 2000s onwards, to understand the continuation of spatial transformations out of step with urban and heritage legislation. Regarding the analysis of these transformations, this study's main contribution is the investigation of licenses processed in the public sphere, revealing the clashes and conflicts between private and public agents for the consolidation of the legality of the real estate production in this new center. For this, administrative processes were consulted at the Department of Norms and Regulations - Municipal Prefecture of Campina Grande (PMCG) and the Archive of the Historical and Artistic Heritage Institute of Paraíba (IPHAEP). The set of collected data, along with the adopted theoretical and methodological analyses, contributed to understanding an intertwining of public and private efforts to maintain the continuity of real estate interest in the central area of Campina Grande, where the production of legality has proven to be the main tool for this consolidation.